A challenge for Harmonic Serialism with Optimal Interleaving*. Issue 3 (3rd January 2014) - Bonet, Eulàlia
Abstract : This paper examines two related phenomena from Catalan that pose a challenge to a proposal in McCarthy (2012 ) that combines Harmonic Serialism (HS) with the theory of Optimal Interleaving (OI) of Wolf (2009). The first phenomenon, found with stems ending in a sibilant, is the selection of a marked masculine allomorph only before the plural morph, also a sibilant, which prevents an OCP violation. The second, phrasal, phenomenon is restricted to one dialect of Catalan: the plural morpheme is not realised in prenominal position only when it would surface between two consonants. It is shown that, with some crucial modifications on the way spell-out proceeds, HS/OI can account for the two phenomena when they occur separately, but when they co-occur within the same phrase, wrong predictions are made, due to the one-change-at-a-time basic property of HS. These problems do not arise in a parallel OT approach.